Coated tubular electrode for hardfacing of pieces under abrasive wear in the sugar industry - Ortiz Méndez, Tamara M.; Cruz Crespo, Amado; Rodríguez, Manuel; Perdomo González, Lorenzo; Fernández Fuentes, Rafael (Centro Azúcar Journal, 2007)
A coated tubular electrode for hardfacing of pieces which work under abrasive wear conditions in the sugar industry is obtained. The above-mentioned is carried out by the addition in the electrode core of a ferroalloy in powder form, using simultaneously a forming process with butt closing. The obtained tubular wire, in reel form, with diameter 4 mm, is fractioned to longitude of 350 mm and recovered by immersion with a basic type coating. Using the obtained electrode his potential application is study by the evaluation of multi-layer weld and the basic criterion about their possible use under abrasive wear condition were established.